Muscle contributions to maximal single-leg forward braking and backward acceleration in elite athletes. (9th November 2020) - Mateus, Rodrigo B.; Ferrer-Roca, Ventura; João, Filipa; Veloso, António P.
Abstract: Abrupt deceleration is a common practice in several sports, where sudden changes of direction are needed to reach the highest performance level. When inappropriately performed, these actions can impose excessive mechanical loads at the lower limb joints, specifically at the knee and ankle joints, usually associated with increased risk of injury. This work aims to estimate muscle forces and muscle contributions to the acceleration of the center of mass during a rapid maximal single-leg forward braking and backward acceleration task. Fourteen elite male injury-free indoor-sports athletes participated in this work. Scaled generic musculoskeletal models, consisting of 12 segments, 23 degrees of freedom, and 92 muscle-tendon actuators were used in OpenSim software. Due to the nature of the musculoskeletal system, all muscles are considered when joint and segment positions, velocities, and accelerations are calculated, resulting in muscles acting to accelerate joints it does not span. The knowledge of muscle interaction during this multijoint task is important and was achieved through an induced acceleration analysis. The vasti (−9.18 ± 2.09 and −7.63 ± 1.33 N/Kg) were the main contributors to the centre of mass deceleration profile along the anterior/posterior direction, aided by the soleus muscle ( 9.72 ± 2.35 and 9.62 ± 2.07 N/Kg ), which counteracted most of the effects applied by gravity along the vertical direction, during both phases. This study provides a computational approach to quantify the dynamical interactions between muscles and joints during an abrupt anterior/posterior deceleration task, thus giving robust and insightful indicators that can be implemented in injury prevention protocols.